Effect of NPK fertilizer rates and growth regulator concentrations on sweet potato crop yield - Martins Filho, José B. [UNESP]; Costa, Raimundo N. T.; de Sousa, Alan B. O.; Gondim, Rubens S. (FapUNIFESP (SciELO), 2023)
The low mean yield of sweet potato crops in Brazil is related to several inadequate crop management practices. Considering the increasing production of this vegetable, the objective of this work was to evaluate the yield response of sweet potato crops subjected to different NPK fertilizer rates (NPK) combined with different growth regulator concentrations. The experiment was carried out in a randomized block design, with a 5×5 factorial arrangement consisted of 5 NPK fertilizer rates (0, 696, 1044, 1392, and 1740 kg ha-1) combined with 5 growth regulator concentrations (0, 20, 25, 30, and 35 mL L-1). Numbers of total and commercial roots per plant were affected by the factors tested, presenting a linear increase as the rates and concentrations were increased. The highest estimated sweet potato yield was 43 Mg ha-1, which was obtained using a NPK rate of 1522.64 kg ha-1 and a growth regulator concentration of 34.69 mL L-1. The higher NPK rates improved water use efficiency up to a maximum value of 8.1 kg m-3 with application of the NPK rate of 1740 kg ha-1. After determining a fixed yield level, the production factors tested act as imperfect substitutes in some intervals of variation of the inputs.
Níveis de fertilização NPK e efeito de concentrações de regulador de crescimento na produtividade da batata-doce
Keywords: Ipomoea batatas (L.) Lam; Irrigation water yield; Isoquants; Production function